Ignacio de Antioquía, ¿testigo ocular de la muerte y resurrección de Jesús? - Rius-Camps, Josep (Biblica, 1989)
Jerome and the Anglo-Latin version of the letters of Ignatius of Antioch interpreted the passage of IgnSm 3,1 in the sense that Ignatius was an eyewitness to Jesus' resurrection. Modern authors translate this differently, understanding that Ignatius died during the persecution of Trajan. However, both the remote and the immediate contexts require that it be considered a clear proof that it came from Ignatius himself against the Docetists. In the fuller recension, which is of doubtful authority, another passage is preserved (IgnRom 2,2) which may well be authentic, considering the independent transmission of IgnRom with respect to the other letters both in the intermediate and in the fuller recensions. In this case, Ignatius would have been a witness to the Lord's passion as well.